2006
DOI: 10.1177/073724770603100304
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Large-Scale Alternate Assessment Systems and Their Influence on Instruction —What Are the Consequences?

Abstract: In conjunction with the Individuals with Disabilities Education Act of 1997 (IDEA; PL 105-17), the No Child Left Behind Act of 2002 (NCLB; PL 107-110) calls for enhancements to existing assessment and accountability systems within specific timelines. The NCLB Act also stresses the importance of using reliable and valid data for decision making. This study examined the consequential validity of a large-scale alternate assessment system for students with severe cognitive disabilities in one midwestern state. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In examining the consequences of alternate assessments in the 2000s, Kleinert and Kearns (2001) reported that teachers from schools with high student performance on the alternate assessment indicated that the assessments had a positive impact on instruction and the inclusion of students with disabilities in classrooms with students without disabilities, whereas teachers from schools with low performance indicated that the alternate assessment had little impact. Towles‐Reeves et al (2006) evaluated the impact of the use of an alternate assessment on the development of instructional educational plans (IEPs). They found that the impact of the alternate assessment on IEP development was significantly less than its impact on instruction, which may have been due to the lack of an explicit connection between the alternate assessment and IEP development.…”
Section: Consequences For Tests Used For Accountability Purposesmentioning
confidence: 99%
“…In examining the consequences of alternate assessments in the 2000s, Kleinert and Kearns (2001) reported that teachers from schools with high student performance on the alternate assessment indicated that the assessments had a positive impact on instruction and the inclusion of students with disabilities in classrooms with students without disabilities, whereas teachers from schools with low performance indicated that the alternate assessment had little impact. Towles‐Reeves et al (2006) evaluated the impact of the use of an alternate assessment on the development of instructional educational plans (IEPs). They found that the impact of the alternate assessment on IEP development was significantly less than its impact on instruction, which may have been due to the lack of an explicit connection between the alternate assessment and IEP development.…”
Section: Consequences For Tests Used For Accountability Purposesmentioning
confidence: 99%
“…As evidence, TIMSS and PISA scores have been equated with the quality of education in different countries (OECD, 2016b;Tucker, 2011;Zhao, 2016c), resulting in strong media and policy reactions around the world (Baird et al, 2016;Dillion, 2010;Figazzolo, 2009;Gruber, 2006;Sellar & Lingard, 2014;Sjøberg, 2015 As evidence, in China, for instance, only subjects tested by the National College Entrance Exam are taken seriously (Yu & Suen, 2015;Zhao, 2014). And the U.S. has witnessed a trend of curriculum narrowing since the enactment of NCLB in the U.S. (Abu-Alhija, 2007;Albrecht & Joles, 2003;Berliner, 2011;Bowen & Rude, 2006;Klenowski, 2011;Klinger & Rogers, 2011;Popham, 2000;Tienken & Zhao, 2013;Towles-Reeves, Garrett, Burdette, & Burdge, 2006;Volante, 2005Volante, , 2006. In surveys of U.S. classrooms in which students were tested on two core subjects (reading and math), classrooms added between 75 and 150 min weekly to each of the two areas.…”
Section: Distorting Educationmentioning
confidence: 99%
“…The effect of LSA on distorting instruction is clearly evidenced by the increase of instructional time devoted to preparing students for state accountability assessments in the U.S. since NCLB (Menken, 2006). There is also evidence that suggests a significant reduction of time spent in deep learning and other important skills such as creativity, problem-solving, organization of knowledge, self-monitoring skills, and the like (Abu-Alhija, 2007; Albrecht & Joles, 2003; Berliner, 2011; Chudowsky & Pellegrino, 2003; Klenowski, 2011; Klinger & Rogers, 2011; Popham, 2000; Towles-Reeves et al, 2006).…”
Section: Distorting Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the heightened emphasis on increasing access for students with PMD to the general education curriculum, the notion of teaching these students academic skills (e.g., preliteracy and prenumeracy) has received increased attention [16][17][18][19]. Reasons for this attention include improving adult competence, increasing educator's expectations, and providing comprehensive instruction [20][21][22].…”
Section: Introductionmentioning
confidence: 99%